Hearing, speech reception, vocabulary and language: population epidemiology and concordance in Australian children aged 11 to 12 years and their parents. (4th July 2019) - Smith, Julia; Wang, Jing; Grobler, Anneke C; Lange, Katherine; Clifford, Susan A; Wake, Melissa
Abstract : Objectives: To describe the epidemiology and parent-child concordance of hearing, speech reception, vocabulary and language in Australian parent-child dyads at child age 11 to 12 years. Design: Population-based cross-sectional study (Child Health CheckPoint) nested within the Longitudinal Study of Australian Children. Setting: Assessment centres in seven Australian cities and eight regional towns or home visits around Australia, February 2015 to March 2016. Participants: Of all participating CheckPoint families (n=1874), 1516 children (50% female) and 1520 parents (87% mothers, mean age 43.8 years) undertook at least one of four measurements of hearing and language. Outcome measures: Hearing threshold (better ear mean of 1, 2 and 4 kHz) from pure-tone audiometry, speech reception threshold, receptive vocabulary, expressive and receptive languages using a sentence repetition task. Parent-child concordance was examined using Pearson's correlation coefficients and adjusted linear regression models. Survey weights and methods accounted for Longitudinal Study of Australian Children's complex sampling and stratification. Results: Children had a similar speech reception threshold to parents (children mean −14.3, SD 2.4; parents −14.9, SD 3.2 dB) but better hearing acuity (children 8.3, SD 6.3; parents 13.4, SD 7.0 decibels hearing level). Standardised sentence repetition scores were similar (children 9.8, SD 2.9; parents 9.1, SD 3.3) but, as expected, parents had superior receptive vocabularies. Parent-child correlations were higher for the cognitively-based language measures (vocabulary 0.31, 95% CI 0.26 to 0.36; sentence repetition 0.29, 95% CI 0.24 to 0.34) than the auditory measures (hearing 0.18, 95% CI 0.13 to 0.23; speech reception threshold 0.18, 95% CI 0.13 to 0.22). Mother-child and father-child concordances were similar for all measures. Conclusions: We provide population reference values for multiple measures spanning auditory and verbal communication systems in children and mid-life adults. Concordance values aligned with previous twin studies and offspring studies in adults, in keeping with polygenic heritability that is modest for audition but around 60% for language by late childhood.